IKLAN POLITIK DAN MINAT MEMILIH (Studi Korelasional Tentang Pengaruh Iklan Politik Televisi Terhadap Minat Memilih Mahasiswa IKM Pascasarjana FISIPOL UGM) - Rahmatul Hidayat (Jurnal Ilmiah Administrasita', 2015)
This research entitled Politic Advertisement and Vote Interest (correlation study about the influence of politic advertisement on TV toward the vote interest of Communication and Media Science student of FISIPOL UGM). The objective of this research is aims to knowing the relationship of presentation the politic advertisement on TV toward the vote interest. To describe this research, the theories used which is reputed relevant into this research are communication and mass communication, SOR theory, politic advertisement, and vote interest. Correlation method is used in this research which the method is used to examine how far the correlation of a variable with the others. The population in this research are the post graduate students of communication science and media FISIPOL UGM which the age minimum 20 years at the beginning semester consists of 16 students. By using Taroyamane formulas, obtained 14 samples of respondent. Data accumulation technique consists of two ways, by using primer data through the research questioner and directly observation during the research as the field data. And also by using secondary data with literature review and the relevant document to the problem of this research. Data analysis technique by using single table and hypotheses test by rank Spearman correlation formulas. The result shows that founded the correlation between politic advertisement and vote interest.